The Effectiveness of a Leniency Program in Algerian and Comparative Competition Law: New Guidelines - Badi Boukemidja, Nadjiba; Chahed, Ouiza (European Journal of Economics and Business Studies, 2019)
Experience shows that in large cartel cases, there are often problems with proof of participation. More and more sophisticated techniques are being put in place by the conspiratorial companies in order to leave as few traces as possible. Thus, with the clemency programs, the risk of denunciation becomes a reality in the world of cartelists, so that the cartel is destabilized from within. The only way to limit the risks of denunciation is to increase controls on members and to strengthen the system of sanctions. All these measures have a cost, which is not negligible and is included in the cost / benefit calculation. The result of the calculation, negative, can dissuade companies from forming cartels. On the contrary, for the competition authorities, the financial benefits are in principle large. For this, clemency programs can effectively combat this type of behavior.